The impact of the covid-19 pandemic on sports – reporting in the daily newspapers of the Czech Republic - Ondřej Trunečka (Acta Universitatis Carolinae: Kinanthropologica)
The Czech quality (non-tabloid) nationwide daily newspapers never published fewer sports pages during the two first decades of twenty-first century than they did during the COVID-19 pandemic. A reduction in the number of pages devoted to sports and other topics was a logical reaction to the paralysis of professional sports and many other domains of human life. But a comparison of data from the first wave of the pandemic, from March to May of 2020 with the same period in the following years proves that the trend to downsize sports sections continued in many cases. This study applied quantitative content analysis to the Monday editions of the Czech daily newspapers Hospodářské noviny, Lidové noviny, Mladá fronta Dnes, and Právo. It confirmed that the position of sport in the daily newspapers has weakened in the long term, and the pandemic accelerated the tendency, especially in the case of more specialised daily newspapers.